Optimization Of Decolourisation Of Textile Dyes By A Locally Isolated Ligninolytic Fungus - Sim, Han Koh (2007)

(untitled)
Water pollution by textile azo dyes is a serious problem worldwide. Local white-rot fungi isolated from soil and wood samples were screened for the ability to degrade textile azo dyes. Seventy one white-rot fungi isolated from various locations in Peninsular Malaysia such as Selangor, Kelantan, Perak and Terengganu were screened for their ability to degrade four textile azo dyes namely Orange G (C.I. 16230), Ponceau 2R (C.I. 16450), Biebrich Scarlet (C.I. 26905) and Direct Blue 71 (C.I. 34140). Forty five isolates gave positive results with varying degrees of degradation. Based on these results, an unidentified white-rot fungus (Isolate S17-UPM) isolated from Universiti Putra Malaysia (UPM) campus in Selangor was selected for further studies due to its ability to completely degrade all four azo dyes in the shortest time. Nutritional studies on defined solid media showed that Isolate S17-UPM was only able to degrade the four azo dyes under nitrogen-limiting conditions and an additional carbon source in the form of glucose was needed to provide sufficient energy for the degradation to occur. When grown in two-stage liquid culture, Isolate S17-UPM was able to degrade 84 to 99% of 0.2 g/L azo dyes in one to ten days with each dye being degraded at different rates. Orange G was degraded the fastest followed by Ponceau 2R, Direct Blue 71 and Biebrich Scarlet. Generally, azo dye degradation rates were shown to be higher in shake cultures compared to static cultures, with rates almost twice those in static cultures. Isolate S17-UPM degraded the four azo dyes optimally when incubated at temperature between room temperature to 30°C in static cultures. The initial pH of the degradation medium (pH 4.0 to 5.9) had significant effects on the degradation rates, where the highest degradation rate was found to be at pH 4.5. The final pH of all cultures dropped to approximately 4.0. Optimum degradation of the four azo dyes was observed when glucose, sucrose, maltose, lactose and fructose were used separately as additional carbon source. The degradations rates were higher at lower concentrations (0.05 g/L) as compared to higher concentrations (1 g/L) except for Biebrich Scarlet. Assays for lignin-modifying enzymes (LMEs) involved in azo dye degradation showed the presence of laccase (E.C. 1.10.3.2) only while lignin peroxidase (E.C. 1.11.1.14) and manganese peroxidase (E.C. 1.11.1.13) were not detected. Laccase activity profile in static liquid degradation cultures showed correlation to the azo dye degradation profile and was highest in cultures incubated at room temperatures except for Orange G cultures, which was highest at 30 °C. The initial pH of the degradation medium (pH 4.0 to 5.9) did not have any significant effect on laccase activity except in Ponceau 2R and Biebrich Scarlet cultures where it is highest at pH 5.9. Additional carbon sources such as glucose (6C), sucrose (12C), maltose (12C), lactose (12C) and fructose (6C) which were used separately in cultures incubated with Orange G, Ponceau 2R and Direct Blue 71 gave much higher laccase activity compared to other carbon sources used. Dye concentrations ranging from 0.05 to 1.00 g/L have significant effects on the laccase activity especially Ponceau 2R. Staining activities of laccase in non-denaturing sodium dodecyl sulphate- polyacrylamide gel electrophoresis (SDS-PAGE) showed highlighted green bands around 66 kDa. Laccase produced by Isolate S17-UPM during azo dye degradation was partially purified using Macro-Prep High-QTM strong-anion exchanger and SuperoseTM gel filtration column, when 2,2’-azinobis (3-ethylbenzothiazoline-6-sulfonate) (ABTS) was used as the substrate, it was shown to have a Km (app) value of 1.6 mM, Vmax (app) value of 16.5 μmol/min.ml, optimum activity at 55 to 75°C and pH 2.0 to 3.0 while being most stable at room temperature and pH 6.0 to 7.0. Conclusively, an azo dye-degrading fungus was isolated and the decolourisation process was optimized, while the enzyme involve was partially purified and characterized.